Coronary vasomotor dysfunction is associated with worse outcomes in patients with inflammatory disease. (25th November 2020) - Weber, B; Brown, J.M; Divakaran, S; Stevens, E; Hainer, J; Bibbo, C; Taqueti, V; Blankstein, R; Dorbala, S; Massarotti, E; Costenbader, K; Liao, K; et al.
Abstract: Background: Rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and psoriasis (PsO) are common inflammatory conditions with excess cardiovascular (CV) risk compared to the general population. This excess CV risk is associated with traditional risk factors, glucocorticoid treatment, and systemic inflammation. Systemic inflammation perturbs endothelial function and has been linked to coronary vasomotor dysfunction. It is not clear if coronary vasomotor dysfunction would be associated with worse clinical outcomes in systemic autoimmune inflammatory conditions. Purpose: We tested the hypothesis that impaired coronary flow reserve (CFR), which in the absence of flow-limiting obstructive coronary artery disease (CAD) reflects vasomotor dysfunction, among patients with SLE, RA, and PsO is associated with worse clinical outcomes. Methods: We included patients with RA, SLE, and PsO who underwent clinically indicated rest/stress myocardial perfusion positron emission tomography (PET) at a large academic medical center from 2006 to 2019. Patients with an abnormal myocardial perfusion study (summed stress score >3) or left ventricular ejection fraction <40% were excluded. CFR was calculated as the ratio of myocardial blood flow (MBF, ml/min/g) at peak stress compared to the MBF at rest and adjusted for baseline heart rate and blood pressure. Results: Among the 175 patients (median age 65.1 years, 80% female) in the cohort, 24% had SLE, 35% PsO, and 41% RA. There was no difference in mean CFR between patients with RA, SLE, or PsO. Over a median follow-up of 8.5 years after PET, there were 47 deaths. Patients in the lowest and middle tertile (CFR <2.18) had a higher all-cause mortality when compared with the highest (Figure 1), and this association remained significant after adjusting for age and a composite clinical score incorporating sex, symptoms, and CV risk factors (lowest vs. highest tertile: HR 2.8; 95% confidence interval 1.2–6.5; p=0.01). CV risk factors such as diabetes, hypertension, obesity, tobacco use, and a family history of CAD were not significantly different across CFR tertiles, suggesting that inflammatory-disease specific risk factors may contribute to coronary vasomotor dysfunction. Conclusions: In patients with systemic inflammatory disease, coronary vasomotor dysfunction was associated with worse outcomes independent of traditional CV risk factors and may have utility as a marker of CV risk among patients with inflammatory disease. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): 1. 5T32HL094301-02 NIH T32 Training Grant, "Noninvasive Cardiovascular Imaging Research Training Program"